Emerging community-based service models for older adults in urban China: A case study in Zhongshan City, Guangdong Province, China. Issue 2 (3rd April 2019) - Li, Qin; Lin, Wenyi
ABSTRACT: This article examines community service provision for older adults under the context of contracting in Zhongshan City, Guangdong Province, China. Two street communities, which adopt different models of non-competitive contracting and competitive contracting, are used to show how community services are provided for older adults. Implications for the further development of community service contracting for older adults are discussed.